DAMPAK PENDIDIKAN DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA KARYAWAN BRI CABANG MAKASSAR - Zainal Abidin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2014)
This study aims to determine the extent of the implications for education and training can improve employee productivity/labor BRI Bank Branch in Makassar. The methodology used in this research is descriptive - qualitative approach , however, to explain the variables used samples analyzed quantitative case . The results showed bahwaPendidikan and exercise has a positive impact in improving the productivity of bank employees . Employees who do not participate in education and training Bank held only produce half of the supposed productivity. If time can be shortened training education , the cost savings become larger and higher employee productivit . The benefits of education and training for an employee must be on the look significantly. In this case , the size of the benefit is